2016
DOI: 10.1080/21642583.2015.1136801
|View full text |Cite
|
Sign up to set email alerts
|

Plankton nutrient interaction model with effect of toxin in presence of modified traditional Holling Type II functional response

Abstract: A three-dimensional plankton-nutrient interaction model is proposed and analysed which mediated by a toxin-determined functional response. The new functional response is a modification of the traditional Holling Type II functional response by explicitly including a reduction in the consumption of phytoplankton by the zooplankton due to chemical defenses. Our analysis leads to different thresholds in terms of model parameters to find out different steady-states behaviour. It is found that constant nutrient inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Pal et al [9] further considered the threecomponent model with both nonlinear predation functions by zooplankton. Further, the study was also extended from the perspectives of stochastic dynamics and planktonnutrient interactions, respectively [10,11].…”
Section: Complexitymentioning
confidence: 99%
“…Pal et al [9] further considered the threecomponent model with both nonlinear predation functions by zooplankton. Further, the study was also extended from the perspectives of stochastic dynamics and planktonnutrient interactions, respectively [10,11].…”
Section: Complexitymentioning
confidence: 99%
“…Chakraborty and Das 16 have obtained the optimal control for a sustainable phytoplankton‐zooplankton system in the presence of toxicity. Beyond the critical value of constant input nutrients, the system shows a Hopf bifurcation in nutrient‐plankton interaction in the presence of toxin 17 . The influence of Allee effect and rate of toxin release in a toxic‐phytoplankton system is investigated by Han and Dai 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the critical value of constant input nutrients, the system shows a Hopf bifurcation in nutrient-plankton interaction in the presence of toxin. 17 The influence of Allee effect and rate of toxin release in a toxic-phytoplankton system is investigated by Han and Dai. 18 Ji and Wang 19 have demonstrated a detailed study of stability and bifurcation for a nutrient-phytoplankton system and identified the control parameters of phytoplankton blooms.…”
Section: Introductionmentioning
confidence: 99%
“…A two zooplankton and one phytoplankton model with toxicity observed that coefficient of toxin plays an important role for existence of Hopf bifurcation around the interior equilibrium [14]. Chatterjee and Pal [15] studied the effect of toxin in nutrient-plankton model and observed that toxic phytoplankton may change the steady-state behavior. De Silva and Jang [16] observed that the mutual interference of zooplankton diminishes harmful blooms.…”
Section: Introductionmentioning
confidence: 99%